Psychological Factors Affecting Students’ Oral Presentation at the English Education Department of Halu Oleo University - Jabir, Muhammad; Mursalim, Mursalim; Agustina, Sitti (Universitas Halu Oleo, 2022)
This study aimed to find out the psychological problems faced by English Department students of Halu Oleo University in doing an oral presentation. This study employed a descriptive research design. The population was all students at the English Education Department of 2016, consisting of two classes, totalling 79 students. Then, the sample was the students of class B who were programming Speaking II, totalling 42 students using the purposive sampling technique. The researcher collected the data by using a close-ended questionnaire. The closed-ended questionnaire employed inferential statistics to find out the frequencies and percentages and then reported the statistical result followed by the conclusion. The result of this study showed that psychological factors were factors affecting the students psychologically in doing an oral presentation. They were fear of mistakes (42%), anxiety (42%), and lack of motivation (50%). Two factors did not correlate students in doing an oral presentation, namely feeling shy and lacking confidence. The rest three factors positively predicted the students’ ability to do oral presentations, such as fear of mistake, anxiety, and lack of motivation. Moreover, the ways to solve the psychological problems faced by the students in doing a presentation were giving motivation to the students and stimulation to practice in doing a presentation. Therefore, it could be concluded that fear of mistakes, anxiety, and lack of motivation were the psychological factors that affected the students in doing an oral presentation, and students’ problems could be solved by the lecturers.